Simulation of the kinetics of direct coal hydrogenation - Balpanova, N.Zh.; Gyulmaliev, A.M.; Pankin, Yu.N.; Ma, F.; Su, K.; Khalitova, A.I.; Aitbekova, D.E.; Tusipkhan, A.; Baikenov, M.I. (KSU Publ., 2020)
The kinetics of coal hydrogenation from the Shenghua deposit (People's Republic of China) has been studied. To calculate the kinetic parameters, experimental data on the hydrogenation of coal from the Shenghua field have been used. The hydrogenation process was carried out at a pressure of 5 MPa, at temperatures from 350 to 440 ºC using a batch reactor. Tetrahydronaphthalene was used as a solvent and donor in the process of coal hydrogenation. The rate constants were calculated using the random search optimization method and the integral Simpson method. It was found that the previously calculated rate constants of the hydrogenation of Shenghua coal (Runge-Kutt method) differ from our data by one order of magnitude. It is supposed that our calculated values of the rate constants are more reliable and adequate than those obtained by the Runge-Kutt method. The limiting rate of coal hydrogenation is observed for the stage of coal conversion into a mixture of gas and oil.
Көмір гидрогенизациясының кинетикасын модельдеу
Моделирование кинетики прямой гидрогенизации угля
Keywords: kinetics; coal; hydrogenation; Simpson integral method; random search optimization method